2016
DOI: 10.1016/j.stemcr.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

EVA1A/TMEM166 Regulates Embryonic Neurogenesis by Autophagy

Abstract: SummarySelf-renewal and differentiation of neural stem cells is essential for embryonic neurogenesis, which is associated with cell autophagy. However, the mechanism by which autophagy regulates neurogenesis remains undefined. Here, we show that Eva1a/Tmem166, an autophagy-related gene, regulates neural stem cell self-renewal and differentiation. Eva1a depletion impaired the generation of newborn neurons, both in vivo and in vitro. Conversely, overexpression of EVA1A enhanced newborn neuron generation and matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
2
33
1
Order By: Relevance
“…Further Gene Ontology analysis using the BINGO plugin also provided information about the molecular functions and cellular components associated with Eva1a, such as protein binding, and transcriptional factor binding. Furthermore, a previous study of the Eva1a −/− mouse showed that the Pik3ca-Akt-Mtor axis is involved in the EVA1A regulation network [4], which also confirmed our KEGG-based pathway enrichment analysis: the PI3K-Akt signaling pathway, Parkinson's disease, and Alzheimer's disease are all associated with the Eva1a regulation network.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further Gene Ontology analysis using the BINGO plugin also provided information about the molecular functions and cellular components associated with Eva1a, such as protein binding, and transcriptional factor binding. Furthermore, a previous study of the Eva1a −/− mouse showed that the Pik3ca-Akt-Mtor axis is involved in the EVA1A regulation network [4], which also confirmed our KEGG-based pathway enrichment analysis: the PI3K-Akt signaling pathway, Parkinson's disease, and Alzheimer's disease are all associated with the Eva1a regulation network.…”
Section: Discussionsupporting
confidence: 89%
“…5), we may infer that NNT plays an important role in the EVA1A network, mediating the progress of neuronal differentiation regulated by EVA1A. Because Eva1a is an autophagy-related gene, its loss may result in the disruption of neurogenesis during nervous system development [4], and may further reduce of neuronal differentiation in the mature brain. Therefore, Eva1a, NNT, and other related genes may be promising targets for drug discovery and further study of regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggested that alterations in neurogenesis that are caused by Cln5 deficiency are not related to changes in hippocampal apoptosis. However, in addition to apoptosis, other mechanisms, such as autophagy, have been reported to modulate stem cell development and neurogenesis ( Wu et al, 2016 ; Li et al, 2016 ). Given that autophagy impairment is a central feature of the NCLs, it is possible that alterations in neurogenesis and autophagy are linked and should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant reports looking at autophagy in neurogenesis indicated that in the absence of the autophagy gene FIP200, NSCs, NPCs, neuroblasts, and neurons in the hippocampus were dramatically reduced and this was accompanied by p53‐dependent apoptosis and cell cycle arrest . Other autophagy genes such as Beclin1, Ambra1, Atg5, Eva1a1 were shown to be highly expressed in the adult SVZ and were required for self‐renewal, survival, and differentiation of hippocampal neurons . Table summarizes the results of the studies implicating autophagy genes in neurogenesis.…”
Section: Autophagy In Neurogenesismentioning
confidence: 99%